Re-emergence of BTV serotype 4 in North Macedonia, July 2020 - Flannery, John; King, Simon; Rajko-Nenow, Paulina; Popova, Zagorka; Krstevski, Kiril; Djadjovski, Igor; Batten, Carrie; Dzadzovski, Igor (Wiley, 2021)
Bluetongue virus serotype 4 (BTV-4) was confirmed in sheep in North Macedonia in July 2020. The full genome of this BTV-4 strain (MKD2020/06) was shown to be most closely related (99.74% nt identity) to the Greek GRE2014/08 and the Hungarian HUN1014 strains, indicating the re-emergence of this BTV serotype in the Balkan region since it was last reported in 2017.